Use of an earthen clay pot refrigerator with a thermoelectric cooler for extending farm produce shelf life - Patel, Nishigandha Sandeep; Pawar, Sachin; Bhojwani, Virendra (Frontiers in Mechanical Engineering, 2023)
Conventional cold storage systems increase the risk of damage and are no longer used for the long-term storage of agricultural products. Thus, newer affordable and energy-efficient storage systems are required for enhancing the shelf life of farm produce. We investigated the coefficient of performance (COP) of an earthen clay pot refrigerator with a thermoelectric cooler (TEC) and explored cooling strategies to enhance cooling and electrical performance for increasing the shelf life of farm produce. We used MATLAB Simulink to analyze Peltier TEC module efficiency. The intrinsic characteristics, including the Seebeck coefficient (α), thermal conductivity (K), and electrical resistance (R), were determined, forming the basis of the Peltier module in MATLAB Simulink. Thermal characteristics such as COP and cooling capacity were studied as a function of system voltage (Vin) and current (Iin). The model was equipped with a 12 V/6 A, 60 W TEC and was verified by simulation investigation. We also used psychrometric measures (e.g., wet bulb, dry bulb, and dew point temperatures and relative humidity) to determine the extent of wetness or dryness of an object and monitor other temperatures of the clay pot refrigerator. The results revealed that the ambient temperature and cold and hot side temperatures fundamentally affected TEC performance. The TEC extended the shelf life of tomatoes, potatoes, and spinach by 60% compared to ambient conditions, thereby reducing their wastage. In conclusion, earthen refrigeration using TEC doubled the shelf life of farm produce compared to ambient conditions, saving money, resources, labor, and supplies and enabling the development of efficient and environmentally friendly refrigeration systems.